Similar adaptation effects on detection and localization of optic flow patterns - Harvey, B; Braddick, O (Pion Ltd., 2007)
Many models of optic flow processing (eg Perrone and Stone, 1998 Journal of Neuroscience 18 5958-5975) suppose that common neural mechanisms are used to detect optic flow patterns and localize their centres. However, recent neuropsychological (Beardsley and Vaina, 2005 Journal of Computational Neuroscience 18 55-66) and neuroimaging evidence (Koyama et al, 2005 Current Biology 15 2027-2032) suggests a separate cortical area specialized for localizing the centre of flow patterns, possibly important for monitoring self-motion. This is consistent with our findings (Harvey and Braddick, 2006 Perception 35 Supplement, 238) that spatial integration properties for detecting and localizing are quite different. We examined the relation between detection and localization by adapting subjects to rotating, expanding, or contracting motions, and measuring effects on coherence thresholds for both detection and localization tasks. When adaptation and test directions were opposite (eg expansion vs contraction, clockwise vs anticlockwise rotation), thresholds were elevated far more for rotating than for contracting test patterns. Overall, adaptation had similar effects on detection and localization tasks, suggesting that both depend on a common processing stage where adaptation effects occur.